Analysis of Intellectual Capital Developed by Economic Teachers in Pontianak City State High School - Maria Ulfah (STKIP Singkawang, 2019)
This study aims to describe the intellectual capital developed by economic teachers in Pontianak City State High School. The approach used in this study is descriptive qualitative. Data were collected from 10 economic teachers from Pontianak City High School. Data analysis uses descriptive qualitative techniques while data collection uses interviews, observation, and documentation as well as field notes/log book. Intellectual capital developed by economic teachers to improve the quality of graduates by conducting interviews with teachers on the development of intellectual capital, as well as conducting interviews with students and principals as cross-check data. In addition, the researcher also observed the teacher's activities in developing intellectual capital. The results showed that: (1) Intellectual capital developed by economic teachers at Pontianak City Public High School was in the form of competencies, namely MGMP activities, mutual respect, adjusting and helping the work completed assigned by superiors to fellow teachers. Whereas in the form of commitment is trust in the PGRI organization. To control the work developed by the economic teacher by means of independence and freedom of the teacher in making learning plans, controlling the learning and decision-making processes during the learning process.